“Canada will not stand idly by ...”: Ukraine in the Foreign Policy of Canada - Marczuk-Karbownik, Magdalena (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
Ukraine has always had a special place in Canadian foreign policy. Currently, Canada is deeply engaged in supporting Ukraine to restore political and economic stability and to implement democratic reforms. The Government in Ottawa has condemned Russian aggressive policy and the illegal military occupation of Crimea and has taken a variety of steps and initiatives since the beginning of the crisis in Ukraine in 2014 including imposing sanctions, economic and military assistance, and supporting of NATO measures.